Literature Gap on Corporate Governance Mechanisms and Bank Asset Quality - Karaye, Abubakar Ibrahim (UUM Press, 2021)
The paper proposes a framework that captures the impact of board capital on bank assets quality (BAQ) in the Nigerian banking industry. The paper reviews literature on various corporate governance’ mechanisms that are instrumental to BAQ, specifically banks’ non-performing loans (NPLs). Based on the review, this study finds that common variables examined by literature are board size, independence and gender. The study also reveals that limited studies exist on the role of human and social capital of the banks’ board of directors. Therefore, evaluating boards’ human and social capital is likely to capture wider-range of boards’ resources, abilities, and chances of exercising control over the rising NPLs figures. In view of this emphasis, this study advocates the use of agency and resource dependence as well as the human capital theories to examine boards’ influence on NPLs. This is because the human and social capital of the board of directors play vital role in the resources needed by directors to function effectively and develop strategies needed for banks to ensure that their loan portfolios are of good quality.